Significance of Narratology in Expanding Knowledge of Everyday Life for Elementary Students in Wisma Penjaringan Sari Surabaya - Hariyono; Wijaya, Kusuma; Pasopati, Rommel Utungga; Nurdin, Dewi Syifanaya Firdausy; Nafis, Naufal; Wardana, Bima Tri (PT. Gudang Pustaka Cendekia, 2024)
This article exposes the crucial points of narratology to expand knowledge of everyday life. This writing is based on community service done to elementary students in Wisma Penjaringan Sari, Rungkut, Surabaya from 2023 to 2024. Narratology mainly emphasizes matters of narrative structures indicated through perceptions of the cultural world as supported by Tzvetan Todorov. Everyday life is understood as reflections of complex actualizations of plural identities in the sense of the living world. Through explorative approach in qualitative research, this paper digs more understanding of everyday life as stories of experience and taste of the people. Putting focus on narrations of the people, the analysis accentuates more into knowledge of everyday life as a never-ending process. It is a continuous understanding being underlined through meanings of individual experience in everyday life. Furthermore, narrative structures include matters of other individuals as otherness. In conclusion, narratology is significant in expanding knowledge of everyday life especially in widening perspectives of otherness through understanding of own self.